Overlooked technological and societal trends that will level-up our fight against climate change - Beaumont, Maximus L. L. (Frontiers in Climate, 2024)
Our ability to fight COVID-19 demonstrates that where there’s a will, there’s a way. Yet proactive action will not be the single driving force behind us winning a stable and benign environment for our children. This article focuses on the not so obvious yet impactful trends affecting our ability to stave off the worst of climate change. These trends include carbon taxation, climate litigation, AI, space exploration, Direct Air Capture and an ever younger, more motivated demographic. Some trends will affect our efforts in unknown and unpredictable ways, while others will drive them with ever more force over the years to come. Carbon taxation requires a proactive change in government policy, but that change will place implementation in the hands of the free market. As we face an existential crisis never before seen by humanity, perhaps the largest driving force affecting our ability to ensure a healthy planet will be a more engaged public.